A Note on the Asymptotic Stability of Fuzzy Differential Equations - Le, Van Hien (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the stability of solutions of fuzzy differential equations by Lyapunov's second method. By using scale equations and the comparison principle for Lyapunov-like functions, we give sufficient criteria for the stability and asymptotic stability of solutions of fuzzy differential equations.